Konsep Pendidikan Berbasis Akhlak Studi Pemikiran Hafidz Hasan Al-Mas’udi dalam Kitab Taisirul Kholaq - Muhammad Yusuf Hilman; Fadilatul Ismah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the concept of morality-based education formulated by Hafidz Hasan Al-Mas’udi in the classical ethical work Taisirul Kholaq. The findings reveal that Al-Mas’udi constructs a philosophical foundation that positions moral character as the essence of the educational process, emphasizing purification of the soul, the stability of ethical orientation, and the harmony between spiritual and social responsibilities. The text offers a structured framework of moral values covering spiritual devotion, interpersonal ethics, and internal self-discipline, which together form a comprehensive model for character formation. Literature-based evidence from previous studies demonstrates that the application of Taisirul Kholaq significantly contributes to the development of honesty, discipline, respect, and cooperative behavior among students in Islamic educational institutions. The systematic arrangement of values and the emphasis on behavioral habituation make this work relevant for contemporary educational contexts that face rapid sociocultural transformation. Overall, Al-Mas’udi’s moral education framework provides an enduring reference for strengthening character formation, offering theoretical clarity and practical guidance essential for building ethically grounded learning environments.